Open access peer-reviewed chapter

# Fixed Point Theorems of a New Generalized Nonexpansive Mapping

By Shi Jie

Submitted: April 2nd 2019Reviewed: July 5th 2019Published: September 25th 2019

DOI: 10.5772/intechopen.88421

## Abstract

This paper introduces a T−Da mapping that is weaker than the nonexpansive mapping. It introduces several iterations for the fixed point of the T−Da mapping. It gives fixed point theorems and convergence theorems for the T−Da mapping in Banach space, instead of uniformly convex Banach space. This paper gives some basic properties on the T−Da mapping and gives the example to show the existence of T−Da mapping. The results of this paper are obtained in general Banach spaces. It considers some sufficient conditions for convergence of fixed points of mappings in general Banach spaces under higher iterations.

### Keywords

• iteration
• convergence theorems
• nonexpansive mapping
• fixed point
• 2010 MSC: 47H09
• 47H10

## 1. Introduction

In this paper, Eis a Banach space, Cis a nonempty closed convex subset of E, and FixT=xC:Tx=x.

Definition 1.T is contraction mapping if there is r01

TxTyrxyforallxyC.

Definition 2.T is nonexpansive mapping if

TxTyxyforallxyC.

Definition 3.T is quasinonexpansive mapping if

TxTyxyforallxC,yFT.

Definition 4.T:CCis a TDamapping on a subset C, if there is a121, TxTyxyfor all αa1,xC,yCTxα, where CTxα=yCy=1αp+αTppCTppTxx.

In 2008 Suzuki [1] defined a mapping Tin Banach space: 12TxTyxyimplies TxTyxy. And Tis said to satisfy condition (C). Suzuki [1] showed that the mapping satisfying condition (C) is weaker than nonexpansive mapping and stronger than quasinonexpansive mapping.

Suzuki [1] proved the theorem Tis a mapping in Banach space, Tsatisfies condition (C), and {xn} is the sequence defined by the iteration process:

x1=xC,xn+1=1αnxn+αnTxn,E1

then {xn} converges to a fixed point of T.

Suzuki [1] gave this convergence theorem in an ordinary Banach space, and the mapping satisfying condition (C) is weaker than nonexpansive mapping.

In 2016, Thakur [2] proved the theorem Tis a mapping in uniformly convex Banach space, Tsatisfies condition (C), and xnis the sequence defined by iteration process:

x1=xC,xn+1=Tyn,yn=Tzn,zn=1αnxn+αnTxn,E2

then {xn} converges to a fixed point of T.

Thakur [2] claimed that the rate of iteration is fastest of known iterations. However, the disadvantage is that their results must be in uniformly convex Banach space, instead of the ordinary Banach space.

The aim of this article is there exists a generalized nonexpansive mapping, which makes the sequence generated by Thakur’s iteration converge to a fixed point in a general Banach space.

The following propositions are obvious:

Proposition 1.If T is nonexpansive, then T satisfies condition (Da).

Proposition 2.If T is TDamapping, then T is quasinonexpansive.

Proposition 3.Suppose T:CCis a TDamapping. Then, for x,yC:

1. T2xTxTxxforallxC.

2. T2xTyTxyorT2yTxTyxforallx,yC.

Proof:

1. Since TxxTxx,TxCTx1, we have T2xTxTxx.

2. For all x,yC, TxxTyyor TyyTxx.

Then TxCTyαor TyCTxα.

It follows that T2xTyTxyor T2yTxTyx.

Example 1

Tx=1.1x2x3x4,x1=3,0x2x3x4,x13,

where

x=x1x2x3x4,x103,x20,0.01,x30,0.01,x40,0.01.
x1=maxx1+x3x2+x4

Set

x=3000

and

y=2.5000

We see that

TxTy1=1.1>xy1.

Hence, Tis not a nonexpansive mapping.

To verify that Tis a TDamapping, consider the following cases:

Case 1:

α11191,x=x1x2x3x4,x13.y=y1y2y3y4CTxα,

then y13. We have

TyTx=0y2x2y3x3y4x4y1x1y2x2y3x3y4x4=yx

Case 2:

α11191,x=x1x2x3x4,x1=3.y=y1y2y3y4CTxα,

then y10,1.9. We have

TyTx=1.1y2x2y3x3y4x41.11yx

Hence, Tis a TDamapping, and Tis not nonexpansive.

## 2. Fixed point

In this section, we prove convergence theorems for fixed point of the TDamapping in Banach space.

Lemma 1. Let Cbe bounded convex subset of a Banach space B. Assume that T:CCis TDamapping and xn,yn,znare sequences generated by iteration:

x1=xC,xn+1=Tyn,yn=Tzn,zn=1αnxn+αnTxn,E3

where 12<aαnb<1. Then

1. Txn+1xn+1TynynTznznTxnxn.

2. limnTxnxn=limnTynyn=limnTznzn=r0.

Proof: (1) From Proposition 3 and zn=1αnxn+αnTxn, we have

Txn+1xn+1T2ynTynTynyn=T2znTznTznzn=TznTxn+1αnTxnxnznxn+1αnTxnxn=Txnxn.

(2) From (1), we have 0Txn+1xn+1Txnxn. So limnTxnxn=r0. Now, we have limnTxnxn=limnTynyn=limnTznzn=r0.

Lemma 2.Assume that T:CCis a TDamapping and xn,yn,znare sequences generated by iteration (3). 12<aαnb<1. Let umsatisfy u3n2=xn,u3n1=zn,u3n=yn. Then, for all n1,p1

1+k=3n23n+p3βkTu3n2u3n2Tu3n2+pu3n2+k=nn+p121αkTu3n2u3n2Tu3n2+3pu3n2+3p,E4

where

βk=αnk=3n21k3n2

Proof: From Lemma 1, we have

Txn+1xn+1Tznzn=Tzn1αnxnαnTxn1αnTznxn+αnTznTxn1αnTznxn+αnznxn=1αnTznxn+αn2Txnxn.

So, for p=1and all n1

1+β3n2Tu3n2u3n2=1+αnTxnxnTxnxn+11αnTxnxnTxn+1xn+1=Tu3n1u3n2+11αnTu3n2u3n2Tu3n+1u3n+1Tu3n1u3n2+21αnTu3n2u3n2Tu3n+1u3n+1.

(4) holds.

We make the inductive assumption that (4) holds for a given p>1and all n>0and obtain, upon replacing nwith n+1

(1+k=3n+13n+pβk)Tu3n+1u3n+1Tu3n+1+pu3n+1+(k=n+1n+p21αk)(Tu3n+1u3n+1Tu3n+1+3pu3n+1+3p).E5

And obviously

k3n2,Tuk+1TukβkTu3n2u3n2,E6
k>t,TukTutukut.E7

Case 1: p=3m,m1. From (6) and (7)

Tu3n+1+pu3n+1=Txn+m+1xn+1=Txn+m+1Tynxn+m+1yn=Tyn+mTznyn+mzn=Tzn+m1αnxnαnTxn1αnTzn+mxn+αnTzn+mTxn1αnTzn+mxn+αnTzn+mTxn+m+Txn+mTyn+m1++TynTzn+TznTxn=1αnTu3n1+pu3n2+αnk=3n23n2+pTuk+1Tuk1αnTu3n1+pu3n2+αnk=3n23n2+pβkTu3n2u3n2.

It follows that

Tu3n+1+pu3n+11αnTu3n1+pu3n2+αnk=3n23n2+pβkTu3n2u3n2E8

Using (5) and (8), we have

1+k=3n+13n+pβkTu3n+1u3n+11αnTu3n1+pu3n2+αnk=3n23n2+pβkTu3n2u3n2+k=n+1n+p21αkTu3n+1u3n+1Tu3n+1+3pu3n+1+3p.

From 1+k=3n+13n+pβkk=n+1n+p11αkand Tu3n+1u3n+1Tu3n2u3n2, we have

1+k=3n+13n+pβkTu3n2u3n21αnTu3n1+pu3n2+αnk=3n23n2+pβkTu3n2u3n2+k=n+1n+p21αkTu3n2u3n2Tu3n+1+3pu3n+1+3p.

Then

1+k=3n+13n+pβkαnk=3n23n2+pβk1αnTu3n2u3n2Tu3n1+pu3n2+k=nn+p21αkTu3n2u3n2Tu3n+1+3pu3n+1+3p.

It follows that

1+k=3n23n2+pβkTu3n2u3n2Tu3n1+pu3n2+k=nn+p21αkTu3n2u3n2Tu3n+1+3pu3n+1+3p.

Thus, for n,p+1, (4) holds.

Case 2: p=3m+1,m0. From (6) and (7), we have

Tu3n+1+pu3n+1=Tzn+m+1xn+1=Tzn+m+1Tynzn+m+1yn=1αm+n+1xm+n+1+αm+n+1Txm+n+1Tzn
1αm+n+1xm+n+1Tzn+αm+n+1Txm+n+1Tzn1αm+n+1Tym+nTzn+αm+n+1xm+n+1zn1αm+n+1(Tym+nTzm+n+Tzm+nTxn+m++Txn+1Tyn+TynTzn)+αm+n+1xm+n+1zn=1αm+n+1k=3n13n2+pTuk+1Tuk+αm+n+1Tym+n1αnxnαnTxn1αm+n+1k=3n13n2+pβkTu3n2u3n2+αm+n+11αnTym+nxn+αnTym+nTxn1αm+n+1k=3n13n2+pβkTu3n2u3n2+αm+n+11αnTym+nxn+αm+n+1αnTym+nTzm+n+Tzm+nTxm+n++TynTzn+TznTxn=1αm+n+1k=3n13n2+pβkTu3n2u3n2+αm+n+11αnTym+nxn+αm+n+1αnk=3n23n2+pTuk+1Tuk1αm+n+1k=3n13n2+pβkTu3n2u3n2+αm+n+11αnTym+nxn+αm+n+1αnk=3n23n2+pβkTukuk=1αm+n+1k=3n13n2+pβkTu3n2u3n2+αm+n+11αnTu3n1+pu3n2+αm+n+1αnk=3n23n2+pβkTukuk=1αm+n+1+αm+n+1αnk=3n23n2+pβkTu3n2u3n2αn1αm+n+1Tu3n2u3n2+αm+n+11αnTu3n1+pu3n2.

It follows that

Tu3n+1+pu3n+11αm+n+1+αm+n+1αnk=3n23n2+pβkTu3n2u3n2αn1αm+n+1Tu3n2u3n2+αm+n+11αnTu3n1+pu3n2E9

Using (5) and (9), we have

1+k=3n+13n+pβkTu3n+1u3n+11αm+n+1+αm+n+1αnk=3n23n2+pβkTu3n2u3n2
αn1αm+n+1Tu3n2u3n2+αm+n+11αnTu3n1+pu3n2+k=n+1n+p21αkTu3n+1u3n+1Tu3n+1+3pu3n+1+3p.

From 1+k=3n+13n+pβkk=n+1n+p11αkand Tu3n+1u3n+1Tu3n2u3n2, we have

1+k=3n+13n+pβkTu3n2u3n21αm+n+1+αm+n+1αnk=3n23n2+pβkTu3n2u3n2αn1αm+n+1Tu3n2u3n2+αm+n+11αnTu3n1+pu3n2+k=n+1n+p21αkTu3n2u3n2Tu3n+1+3pu3n+1+3p.

Then

1+k=3n+13n+pβk+αn1αm+n+11αm+n+1+αm+n+1αnk=3n23n2+pβkαm+n+11αnTu3n2u3n2Tu3n1+pu3n2+k=nn+p21αkTu3n2u3n2Tu3n+1+3pu3n+1+3p.

It follows that

1+k=3n23n2+pβkTu3n2u3n2Tu3n1+pu3n2+k=nn+p21αkTu3n2u3n2Tu3n+1+3pu3n+1+3p.

Thus, for n,p+1, (4) holds.

Case 3: p=3m+2,m0. From (6) and (7), we have

Tu3n+1+pu3n+1=Tyn+m+1Tynyn+m+1yn=Tzn+m+1Tznzn+m+1znzn+m+11αnxnαnTxn1αnzn+m+1xn+αnzn+m+1Txn=1αn1αn+m+1xn+m+1+αn+m+1Txn+m+1xn+αn1αn+m+1xn+m+1+αn+m+1Txn+m+1Txn
1αn1αm+n+1xn+m+1xn+αm+n+1Txn+m+1xn+αn1αm+n+1xn+m+1Txn+αm+n+1Txn+m+1Txn1αnαm+n+1Txn+m+1xn+1αm+n+11αn+αm+n+1αnxn+m+1xn+αn1αm+n+1Tyn+m+1Txn1αnαm+n+1Txn+m+1xn+1αm+n+11αn+αm+n+1αnTyn+mTzn+m++TznTxn+Txnxn+αn1αm+n+1Tyn+m+1Tzn+m+1++TynTzn+TznTxn1αnαm+n+1Txn+m+1xn+1αm+n+11αn+αm+n+1αnk=3n23n3+pTuk+1Tuk+Tu3n2x3n2+1αm+n+1αnk=3n23n3+pTuk+1Tuk1αnαm+n+1Txn+m+1xn+1αm+n+11αn+αm+n+1αnk=3n23n2+pβkTxnxn+1αm+n+1αnk=3n23n3+pβkTxnxn1αnαm+n+1Tu3n1+pu3n2+1αm+n+1+αnαm+n+1k=3n23n2+pβkαn1αm+n+1Tu3n2u3n2.

It follows that

Tu3n+1+pu3n+11αnαm+n+1Tu3n1+pu3n2+1αm+n+1+αnαm+n+1k=3n23n2+pβkαn1αm+n+1Tu3n2u3n2E10

Using (5) and (10), we have

1+k=3n+13n+pβkTu3n+1u3n+11αnαm+n+1Tu3n1+pu3n2+1αm+n+1+αnαm+n+1k=3n23n2+pβkαn1αm+n+1Tu3n2u3n2+k=n+1n+p21αkTu3n+1u3n+1Tu3n+1+3pu3n+1+3p.

From 1+k=3n+13n+pβkk=n+1n+p21αkand Tu3n+1u3n+1Tu3n2u3n2, we have

1+k=3n+13n+pβkTu3n2u3n21αnαm+n+1Tu3n1+pu3n2+1αm+n+1+αnαm+n+1k=3n23n2+pβkαn1αm+n+1Tu3n2u3n2+k=n+1n+p21αkTu3n2u3n2Tu3n+1+3pu3n+1+3p.

Then

(1+k=3n+13n+pβk1αm+n+1+αnαm+n+1k=3n23n2+pβkαn1αm+n+11αnαm+n+1Tu3n2u3n2Tu3n1+pu3n2+k=nn+p21αkTu3n2u3n2Tu3n+1+3pu3n+1+3p.

It follows that

1+k=3n23n2+pβkTu3n2u3n2Tu3n1+pu3n2+k=nn+p21αkTu3n2u3n2Tu3n+1+3pu3n+1+3p.

Thus, for n,p+1, (4) holds. This completes the induction.

Lemma 3.T:CCis a TDamapping, TxxTyy. Then

xTy3Txx+xy.

Proof: Since TxxTyy, we have TxCTyα. Then

T2xTyTxy.

It follows that

xTyxTx+T2xTx+T2xTy.

From Proposition 3, we have

xTy2Txx+Txy2Txx+Txx+xy=3Txx+xy.

Theorem 1.Assume that T:CCis a TDamapping and xn,yn,znare sequences generated by iteration (3), 12<aαnb<1. Then limnTxnxn=0.

Proof: Since C is bounded, there must exists d>0,for every xC,xd. Let umsatisfy u3n2=xn,u3n1=zn,u3n=yn. From Lemma 1, limkTukuk=r0. Assume r>0. Let εsatisfy

e61bdr+1ε<r

and choose nso that for every p>0

Tu3n2u3n2Tu3n2+3pu3n2+3p<ε.

Now choose pso that rk=3n23n+p4βkdrk=3n23n+p3βk.

Since 12<aαnb<1, for every k,t, we have 1+αk<3αk,αt<2αk. From Lemma 2and rTu3n2u3n2, we have

d+rr1+k=3n23n+p3βk1+k=3n23n+p3βkTu3n2u3n2Tu3n2+pu3n2+k=nn+p121αkTu3n2u3n2Tu3n2+3pu3n2+3p<d+k=nn+p121αkε=d+eΣk=nn+p1ln1+1+αk1αkεd+eΣk=nn+p11+αk1αkεd+e31bΣk=nn+p1αkεd+e61bΣk=3n23n+p3βkεd+e61bΣk=3n23n+p4βk+1ε<d+e61bdr+1ε<d+r.

This is a contradiction. So limkTukuk=0. That is to say, limnTxnxn=0. This completes the proof.

Theorem 2.Assume that T:CCis a TDamapping and xnis generated by iteration (3), 12<aαnb<1. Then the sequence xnconverges to a fixed point of T.

Proof: Since Cis compact, there exists a subsequence xnkxnwhich converges to some zC. By Lemma 3, we have xnkTz3Txnkxnk+xnkz. Since limnkTxnkxnk=0and limnkxnkz=0, we have limnkxnkTz=0. This implies that z=Tz. On the other hand, from Proposition 3

xn+1zynzznzαnTxnz+1αnxnzxnz.

So, limnxnzexists. Therefore, limnxnz=0. This completes the proof.

chapter PDF
Citations in RIS format
Citations in bibtex format

## More

© 2019 The Author(s). Licensee IntechOpen. This chapter is distributed under the terms of the Creative Commons Attribution 3.0 License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

## How to cite and reference

### Cite this chapter Copy to clipboard

Shi Jie (September 25th 2019). Fixed Point Theorems of a New Generalized Nonexpansive Mapping, Functional Calculus, Kamal Shah and Baver Okutmuştur, IntechOpen, DOI: 10.5772/intechopen.88421. Available from:

### Related Content

#### Functional Calculus

Edited by Kamal Shah

Next chapter

#### Folding on the Chaotic Graph Operations and Their Fundamental Group

By Mohammed Abu Saleem

#### Structure Topology and Symplectic Geometry

Edited by Kamal Shah

First chapter

#### A Review Note on the Applications of Linear Operators in Hilbert Space

By Karthic Mohan and Jananeeswari Narayanamoorthy

We are IntechOpen, the world's leading publisher of Open Access books. Built by scientists, for scientists. Our readership spans scientists, professors, researchers, librarians, and students, as well as business professionals. We share our knowledge and peer-reveiwed research papers with libraries, scientific and engineering societies, and also work with corporate R&D departments and government entities.